Stealing each other's clothes. (Economist, 2001)
Reports on Sun Microsystems, manufacturer of server computers that run on the Unix operating system. Mention of Sun's Sun Fire 15K, which competes with mainframe computers that dominate corporation's data centers; Reasons that Sun is interested in the mainframe market; Competition from International Business Machine (IBM) with its Unix server called Regatta; Possibility that Linux will become the standard server operating system for the industry.